The relationship between sleep quality and depressive symptoms in older adults: the mediated role of muscle strength (dynapenia) - Ning Wei; Xinxin Wang; Mengyu Lyu; Ling Chen (BMC Public Health)
Abstract Background The association between sleep quality and depressive symptoms was established, which could be varied by some mediators. Muscle strength might be a potential mediator for this association. The purpose of this study was to explore the mediating role of muscle strength in the relationship between sleep quality and depressive symptoms among the older individuals with or without dynapenia. Methods Three hundreds and nine older adults were allocated into two groups: dynapenia and non-dynapenia groups. The handgrip strength was assessed by the hand-held dynamometer. The quality of sleep and depressive symptoms were evaluated using Pittsburgh Sleep Quality Index and the 15-item Geriatric Depression Scale, respectively. The ProcessV3.3 was used to estimate the simple mediation model, with controlled covariates and centralized variables. Results In both dynapenia (n = 142) and non-dynapenia (n = 167) groups, the quality of sleep was positively correlated to depressive symptoms, while negatively related to muscle strength (p < 0.05). Meanwhile, depressive symptoms were negatively correlated to muscle strength (dynapenia: p = 0.001; non-dynapenia: p < 0.001). Muscle strength only acted as a mediator accounting for 10.04% of the total effect of sleep quality on depressive symptoms in the older individuals with dynapenia. No mediating role was found in the effect of depressive symptoms on sleep quality in both dynapenia and non-dynapenia group. Conclusion Muscle strength was a mediator in the one direction of the relationship between sleep quality and depressive symptoms (the effect of PSQI on GDS-15) in older individuals with dynapenia.